Develando los sentidos de la motricidad en Colombia (2005)
ABSTRACT: With the suspicion that in the area of the physical education he exists significant breaches between the reality (formal education) and the intentions and mission that the discipline in the human development has, a group of investigators in national network with international intervention , drew up a project of study with the objective to reveal "the senses of the human movement, from the vision of the actors of the Physical education in Colombia", like departure poi nt to invite to a change and rupture of paradigms in this field. In the study, the set of perceptions, educational speeches is understood by "Senses", experiences and practices that the teachers of the physical education in Colombia have in relation to the human movernent that surpass from its complexity the understanding and meaning of the human, the bio- physiologic concept of the body and instrumental mechanical dualism that is assigned to him to the movement in historical course of the discipline.